Participatory ranking of fodders in the western hills of Nepal - Tamang, Bir Bahadur; Shah, Manoj Kumar; Dhakal, Bishnu; Chaudhary, Pashupati; Chhetri, Netra (Journal of Agriculture and Natural Resources, 2020)
Fodder is an important source of feed of the ruminants in Nepal. In the mid hills of Nepal, farmers generally practice integrated farming system that combines crop cultivation with livestock husbandry and agroforestry. Tree fodders are good sources of protein during the forage and green grass scarcity periods especially in dry season. Local communities possess indigenous knowledge for the selection of grasses and tree fodders at different seasons in mid hills of western Nepal. A study was conducted on the perception of farmers with respect to selection of fodder species in eight clusters in Kaski and Lumjung districts that range 900-2000 meter above sea level and receive average precipitation of 2000- 4500mm per annum. During the fodder preference ranking, farmers prepared the inventory of fodders found around the villages and nearby forests and selected top ten most important fodders in terms of their availability, palatability, fodder yield, milk yield and milk fat yield. In total, 23 top ranking fodders species were selected from the eight clusters. These fodder species were also ranked using pairwise ranking and weighted scoring methods and ranking was done on the basis of merit numbers obtained from weighted scores. The analysis revealed Artocarpus lakoocha as best tree fodder followed by Ficus semicordata, Thysanolena maxima and Ficus calvata. Similarly, the calendar of fodders trees for lopping season and the best feeding time was prepared on the basis of farmers’ local knowledge. This study suggests strategies for promotion of locally preferred tree fodder species and supplementing tree fodder with feed in different seasons depending on their availability and local preferences.